Composite materials design and applications - Gay, Daniel (CRC Press, Taylor & Francis, 2023)
For decades, Composite Materials: Design and Applications has guided readers on the efficient design of structural composite parts and has illustrated challenges encountered in modern engineering practice. The Fourth Edition of this perennial best-seller, now including a foreword by Professor Stephen Tsai, retains its pedagogical structure, featuring a technical level that rises in difficulty as the text progresses, while allowing each part to be explored independently, but has been updated to mirror recent advances and developments in manufacturing processes and applications. Gives numerous examples of the pre-sizing of composite parts, processed from industrial cases and reworked to highlight key information. Provides a design method to define composite multilayered plates under loading, along with all numerical information needed for implementation. Includes test cases for the validation of computer software using finite elements. Proposes original study of composite beams of any section shapes and of transverse shear behavior of laminates, leading to technical formulations that are not found in the literature. Reflects the latest manufacturing processes and applications in the aerospace, automotive, naval, wind turbine, and sporting goods industries, and now features new details on the recycling of composites and additive manufacturing. Offers new coverage of ceramic-matrix composites and new concepts for design of laminates, including Double-Double and tapered laminates by means of Tsai homogenization. This book serves as a textbook for advanced students studying composite materials design, as well as a handy reference for industry professionals working with composite materials.